OK, think about a sphere in 3D and a plane tangent to it at a point. The line from the centre of the sphere to the tangent point is normal to the plane - that's the key to this stuff. Also, remember that a plane in form Ax + By + Cz + D = 0 has normal vector (A, B, C).
For the first question, the centre of the sphere is at (1, 2, 3) and the tangent point is (2, 4, 5), so the vector from one to the other is (1, 2, 2). This is normal to the tangent plane, so the tangent plane has form
x + 2y + 2z + D = 0
and contains the point (2, 4, 5), so put this in:
2 + 2(4) + 2(5) + D = 0 => D = -20. So the plane is
x + 2y + 2z - 20 = 0.
For the second one, all we need to find is the radius of the sphere. There is a long but straightforward way to do it, and a shorter but trickier way. Here's the first way:
Let the tangent point be (x, y, z). Then we know the vector (x-2, y-1, z-3) and the vector (3, -4, 2) are both normal to the plane, so they must be scalar multiples:
(x-2, y-1, z-3) = k(3, -4, 2) for some k
=> x = 3k + 2, y = -4k + 1, z = 2k + 3
We also know it is on the plane, so 3x - 4y + 2z = 12
=> 3(3k + 2) - 4(-4k + 1) + 2(2k + 3) = 12
=> 9k + 6 + 16k - 4 + 4k + 6 = 12
=> 29k = 4, k = 4/29
So x-2 = 12/29, y-1 = -16/29, z-3 = 8/29.
The equation of the sphere is
(x-2)^2 + (y-1)^2 + (z-3)^2 = r^2
Substituting in we get r^2 = (12/29)^2 + (-16/29)^2 + (8/29)^2
= 464 / 841 = 16/29.
So the full equation is
(x-2)^2 + (y-1)^2 + (z-3)^2 = 16/29.
For the shorter method, note that we only need to find the radius of the sphere to have the full equation; this will be the distance from the centre of the sphere to the plane.
Let n = (3, -4, 2), so the plane has vector equation n . x = 12. Now ||n|| = sqrt(3^2 + (-4)^2 + 2^2) = sqrt(29). Moving distance 1 along the direction of n will give an increase of sqrt(29) in the value of n . x. At the centre of the sphere n . x = 6 - 4 + 6 = 8, so we need to increase this by 4 to get to the plane. This will require moving a distance 4 / sqrt(29), which is therefore the radius of the sphere. So the equation is
(x-2)^2 + (y-1)^2 + (z-3)^2 = (4 / sqrt(29))^2 = 16/29.
2007-01-15 12:51:22
·
answer #1
·
answered by Scarlet Manuka 7
·
1⤊
0⤋
3y + 2Z = 12 y - z = 9. from the 2d: y = z+9 exchange into the 1st 3(z+9) + 2z = 12 3z + 27 + 2z = 12 5z + 27 = 12 subtract 27 from the two facets 5z = -15 divide by using 5 z = -3 y = z+9 = -3+9 = 6 the respond is C.
2016-10-31 05:22:25
·
answer #2
·
answered by mosesjr 4
·
0⤊
0⤋
Dude.
Put the pencil down and walk away from the desk.
What could this possibly solve?
I dont get it-adding nubers with letters-WHAT- just add numbers.
why ad them anyway.
Take a Break
2007-01-15 12:43:06
·
answer #3
·
answered by pickologist 3
·
0⤊
2⤋